Aplikasi Manajemen Multi Proyek menggunakan Metode Scrum - Andri Wijaya Kusuma; Nurudin Santoso; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In a software house, project managers took an important role in managing and making software. The project manager for each project is given to different people. But it is also possible for someone to act as a project manager on more than 1 project at the same time. For how to report from each worker to the project manager also varies. There are those who hold meetings once a week, or on weekdays before going home, or the project manager must ask to each member. So, the project manager cannot monitor every progress of the latest workmanship of the team members at all times and also cannot directly assign assignments to the team members as well as team members cannot know the tasks that must be done if the previous task has been completed. To solve the problem, the author developed a multi-project management application that can manage work activities carried out, and monitor the progress of the project. The application applies the Scrum method, in which there is an iteration for the process of working on the project. In developing the application the author uses the waterfall model. Based on the testing performed, unit testing, integration testing, and validation testing produced a valid value in the test case that has been done. In compatibility testing shows that the application can run optimal on 9 of the 11 browser versions tested.